Audyt wewnętrzny jako element corporate governance - Winiarska, Kazimiera (The Internal Audit as an Element of Corporate Governance, 2005)
While being defined, the rules of corporate governance were based on the good practice of corporate supervisory, to which the Cadbury Report, Greenbury and Hampel Reports, Combined Code and Turnbull Report might be included. Sudden and unexpected collapse of some large enterprises (Enron, WorldCom, Anders, Parmalat, Ahold) and the incorrectness and frauds that were discovered then caused that the Sarbanes-Oxley Act was passed by the United States Congress. The Act is more strict than British reports in the sphere of responsibility and duties of people managing enterprises. The Sarbanes-Oxley Act includes the obligation of creating an Audit Committee which supervises internal auditors' work. The verification of efficiency of the internal control, risk management and organisation management is executed by the Audit Committee on the order of Supervisory Board.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 352-358